The Urgency Of Guidance And Counselling In The Process Of Cultural Enculturation - Maswar, Rezi; Irman, Irman; Lena, Roy; Justine, Kose (Yayasan Minang Darussalam, 2022)
Cultural enculturation should continue to develop from generation to generation. However, what happened was cultural acculturation and assimilation that made the enculturation process almost disappear as a legacy that must be passed down from generation to generation. This study aims to describe the urgency of guidance and counseling in cultural enculturation. This study uses a literature review method. From the results of these scientific works, it is explained that counseling guidance is very urgent in cultural enculturation. This is because guidance and counseling guides individuals to understand and understand themselves that they are unique individuals and have a culture that must be maintained.